The Effect of Mineral and Organic Fertilizers on Hot Pepper Yield in Different Numbers - Ismailov Makhsetbay Embergenovich; Jamalov Sultanbek (Researchparks Publishing, 2022)
A field experiment was conducted in order to determine whether it is possible to grow hot pepper under organic farming conditions in the saline soil of the central zone of the Republic of Karakalpakstan. In it, the effect of mineral, organic fertilizers and biostimulant on the yield of hot pepper was studied in different basic numbers (33.0, 50.0 and 66.0 thousand units). 49.7-55.6 c/ha and 63.1 c/ha when using organic fertilizers at the rate of 40 and 60 t/ha and an additional 2 l/ha of biostimulant provided to receive. In this case, the high indicator is observed when the base number is 50,000 units.